Morphological variation and distribution of free neuromasts during half-smooth tongue sole Cynoglossus semilaevis ontogeny - 马爱军 商晓梅 周洲 王新安 孙志宾 崔文晓 夏丹丹 马本贺 (Chinese journal of oceanology and limnology, 2017)
This study was conducted to clarify the distribution and morphology of free neuromasts during the development of half-smooth tongue sole （Cynoglossus semilaevis） using scanning electron microscopy. During development, （1） the apical surface of free neuromasts changed in shape from a circle to a four-poiut star; （2） the external structure changed from being level with the epidermis to papilla-like above the level of the epidermis; （3） the neuromast cupula changed from cylindrical to blade-shaped; （4） the free neuromasts went from occurring singly to being in clusters of a few single organs; （5） the arrangement changed from a linear array to no discernable pattern; （6） there was a significant increase in the number of free neuromasts after metamorphosis. In adult C. semilaevis, free neuromasts were only observed on the abocular side of the head. Thus, there were more free neuromasts located on the abocular side of the head with a higher concentration around the anterior nostril and mouth, which may have a mechanical sensory function to help locate food as an adaptation to a benthic mode of life.